PENGARUH SAFETY SIGN TERHADAP PERILAKU AMAN PEKERJA PADA BAGIAN PRODUKSI PT. JAKARANA TAMA MIE GAGA CAB. MEDAN KEC. MEDAN AMPLAS - Irmayani, Irmayani; Parinduri, Anggi Isnani; Hayati, Kardina (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The progress of formal industry is accompanied by the use of technology used in the production process and has the risk of harm to aspects of occupational safety and health as well as the work environment. The promotion of occupational safety and health visually using the media safety sign is an effective way to improve workers' safe behavior. Quantitative research with a quasi-experimental approach to the design of one group pretest posttest research. Using a total sampling technique with a population of 50 worker samples. Data collection using questionnaires and interviews. The statistical test in this study uses the Wilcoxon signed rank test to see differences in the results of the pre-test and post-test, the results of the study indicate that there is an effect of providing safety sign to the safety behavior of workers in the production section with the results of p (0.007) â‰¤ Î± (0.05) and can it was concluded that the posttest results experienced an increase of 5 respondents (5%) safety behaviour. The advice that can be given is that workers should further enhance safe behavior in work and pay attention to safety signs that exist in the work environment, especially in the production department and for companies to have OHS (occupational health safety), and provide OHS training and guidance on OHS to improve the abilities and skills of workers, especially in the section production to safety behavior.